Insights Into the Role of Endoplasmic Reticulum Stress in Infectious Diseases - Choi, Ji-Ae; Song, Chang-Hwa (Frontiers in Immunology, 2020)
The endoplasmic reticulum (ER) is the major organelle in the cell for protein folding and plays an important role in cellular functions. The unfolded protein response (UPR) is activated in response to misfolded or unfolded protein accumulation in the ER. However, UPR does not always successfully alleviate the ER stress. If UPR fails to restore ER homeostasis, apoptosis is induced. ER stress plays an important role in innate immune signaling in response to microorganisms. Dysregulation of UPR signaling contributes to the pathogenesis of a variety of infectious diseases. In this review, we summarize the contribution of ER stress to the innate immune response to invading microorganisms and its role in the pathogenesis of infectious diseases.